Controversial poetry 1400-1625 - Kessler, Judith, 1980-; Kundert, Ursula; Oosterman, Johan, 1962- (Radboud studies in humanities, 2020)
"Controversial poetry played a crucial role in dealing with religious, political, and scholarly conflicts from 1400 until 1625. This volume analyses roles and functions of Latin, Italian, Dutch, German, Scots, and Hungarian poetry in specific historical controversies. A media theory of poetical impact is proposed by Franz-Josef Holznagel and Dieuwke van der Poel. Levente Seláf, Philipp Steinkamp, and Guillaume van Gemert examine the genres sung in wars, and in rulers' controversies. Judith Kessler, Dirk Coigneau, Juliette Groenland, and Regina Töpfer analyse how female and male rhetoricians and humanists use verse in religious, municipal, and educational conflicts. Signe Rotter-Broman, Samuel Pakucs Willcocks, and Alasdair MacDonald explain how reception strategies can shape cultural and political identities."--